Modelling of heat and mass transfer at oscillating drying in mobile grain dryer - A. V. Golubkovich; I. A. Pekhal’Skiy; I. D. Lukin; R. A. Marin (Сельскохозяйственные машины и технологии, 2015)
Features of heat and mass transfer in a grain dryer and in a kernel at oscillating drying, one of energy saving technologies, were considered. In comparison with widespread in agriculture technologies at constancy of agent of drying temperatures it allows to reduce energy consumption by 20 percent at preservation or increase in nameplate capacity of the dryer. It was noted that improvement of technology and technical means of drying are possible at mathematical modeling of processes of heat and mass transfer in a grain dryer with the subsequent transition to a grain layer. The basic conditions of ensuring safe seeds drying at an oscillating method are decrease in duration of influence of the high-temperature drying agent and increase in its temperature potential that increases intensity of process and reduces energy consumption. Calculated Characteristics of the grain drying mode and parameters of the dryer, including duration of the periods of oscillating drying, temperature highly- and the low-temperature agent of drying, the lying duration, height of the over-the-dryer hopper used as a heat and mass exchanger in the mobile dryer. Transfer of moisture and heat in a kernel and it cover at a bigger admissible temperature of grain heating in mathematical models in comparison with method at an invariable temperature of the drying agent were considered. Key parameters of process and the device in a mobile grain dryer were determined. To increase efficiency and energy saving drying should be carried out at a temperature of grain heating close to maximum permissible. Height of the over-the-dryer hopper) should be not less than 0.7 m.